Plants Under Metal and Metalloid Stress Responses, Tolerance and Remediation (Springer Singapore, 2018)
In the industrial era, the most important potential threat to crop production is abiotic stress, including toxic metal/metalloid stress. Growing populations and rapid industrialization lead to the generation and release of huge amounts of toxic metals/metalloids into the environment, altering plant physiological processes and reducing yields. In the last few decades, there has been extensive research to elucidate the mechanisms of tolerance to metal/metalloid toxicity and ways to improve the defense system in plants. Use of exogenous photoprotectants such as osmoprotectants, plant nutrients, phytohormones, signaling molecules, antioxidants, amino acids and organic acids are widely being used to improve plants' tolerance to metal/metalloid stress. Recently, phytoremediation approaches have been effectively employed to remediate metal/metalloid pollution. This book presents the latest insights into plant responses and tolerance in plants grown under metal/metalloids stress to provide a better understanding of the topic and the future outlook. .